Prolonging Nephrogenesis in Preterm Infants: A New Approach for Prevention of Kidney Disease in Adulthood? (Iranian Journal of Kidney Diseases, 2015)
Chronic kidney disease represents a dramatic worldwide resource-consuming problem. This problem is of increasing importance even in preterm infants, since nephrogenesis may go on only for a few weeks (4 to 6 weeks) after birth. Recent literature focusing on traditional regenerative medicine does not take into account the presence of a high number of active endogenous stem cells in the preterm kidney, which represents a unique opportunity for starting regenerative medicine in the perinatal period. Pluripotent cells of the blue strip have the capacity to generate new nephrons, improving kidney function in neonates and potentially protecting them from developing chronic kidney disease and end-stage renal disease in adulthood. There is a marked interindividual neonatal variability of nephron numbers. Moreover, the renal stem/progenitor cells appear as densely-packed small cells with scant cytoplasm, giving rise to a blue-appearing strip in hematoxylin-eosin-stained kidney sections ("the blue strip"). There are questions concerning renal regenerative medicine: among preliminary data, the simultaneous expression of Wilms tumor 1 and thymosin β4 in stem/progenitor cells of the neonatal kidney may bring new prospects for renal regeneration applied to renal stem cells that reside in the kidney itself. A potential approach could be to prolong the 6 weeks of postnatal renal growth of nephrons or to accelerate the growth of nephrons during the 6 weeks or both. Considering what we know today about perinatal programming, this could be an important step for the future to reduce the incidence and global health impact of chronic kidney disease.